Influence of organic amendments on dissipation and leaching potential of penoxsulam under laboratory conditions. Issue 9 (15th July 2022) - Kaur, Pervinder; Kaur, Harshdeep; Bhullar, Makhan Singh
ABSTRACT: Application of organic amendments to soil is a frequent agricultural practice for avoiding the irreversible soil degradation. However, this practice could modify the behaviour of applied herbicide. This study evaluates the impact of organic matter (OM) amendment on dissipation and leaching of penoxsulam. The addition of OM amendments enhanced the degradation rate of penoxsulam and 91.27, 89.46, 89.05 and 81.03% degradation was observed in press mud (PM), farmyard manure (FYM), poultry manure (POM) and vermicompost (VC)-amended soils after 30 days in comparison to 67.31% degradation in unamended soil. PM OM amendment was most effective in enhancing the degradation of penoxsulam. Three metabolites of penoxsulam were detected and depending upon the type of amendment there was variation in appearance and persistence of these metabolites in soil. The analysis of penoxsulam at different soil depths showed that it leached up to the depth of 30–40 cm in unamended and VC and FYM amended soil whereas to a depth of 20–30 cm in POM and PM-amended soil. The residual amounts of penoxsulam at lower depths were lesser in the amended soils than in unamended soil. None of the leachate fractions showed the presence of penoxsulam residues. The use of OM amendment in soil is an effective management practice for controlling potential pollution caused by penoxsulam to the environment.